2010
DOI: 10.1007/s12031-010-9449-3
|View full text |Cite
|
Sign up to set email alerts
|

Cortical 5HT2A Receptor Function under Hypoxia in Neonatal Rats: Role of Glucose, Oxygen, and Epinephrine Resuscitation

Abstract: Neonatal hypoxia induces brain injury through alterations in neurotransmitters and its receptors. Molecular processes regulating serotonergic receptors play an important role in the control of respiration under hypoxia. The present study evaluates the serotonergic regulation of neonatal hypoxia and its resuscitation methods. Receptor binding assays and gene expression studies were done to evaluate the changes in 5HT(2A) receptors and its transporter in the cerebral cortex of hypoxic neonatal rats and hypoxic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Hypoxia upregulates cortical 5-HT2ARs (Anju et al, 2011) and the 5-HT2AR agonist psychedelic N,N-Dimethyltryptamine (DMT) exerts neuroprotective effects in cells exposed to hypoxic conditions, leading scholars to suggest endogenous DMT may be released as an adaptive response to physiological stress (da Silva Soares et al, 2019; Szabo et al, 2016). A recent study observed increased DMT levels in rat visual cortex following cardiac arrest (Dean et al, 2019), a finding that supports the hypothesized role of endogenous DMT in NDEs (Strassman, 2000; Timmermann et al, 2018).…”
Section: Serotonin Stress and The 5-ht2armentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxia upregulates cortical 5-HT2ARs (Anju et al, 2011) and the 5-HT2AR agonist psychedelic N,N-Dimethyltryptamine (DMT) exerts neuroprotective effects in cells exposed to hypoxic conditions, leading scholars to suggest endogenous DMT may be released as an adaptive response to physiological stress (da Silva Soares et al, 2019; Szabo et al, 2016). A recent study observed increased DMT levels in rat visual cortex following cardiac arrest (Dean et al, 2019), a finding that supports the hypothesized role of endogenous DMT in NDEs (Strassman, 2000; Timmermann et al, 2018).…”
Section: Serotonin Stress and The 5-ht2armentioning
confidence: 99%
“…Modern therapeutic techniques such as breathwork (Brown and Gerbarg, 2005; Grof and Grof, 2010) and whole-body hyperthermia (Hanusch et al, 2013; Janssen et al, 2016) continue to reinforce the idea that physiological stress or dysregulation can lead to meaningful changes in mental states and have been found to interface with the serotonin system (Anju et al, 2011; Buchanan et al, 2015; Pawlyk et al, 2006). The cross-cultural and recurring practice of asceticism cannot be explained as a purely culturally contingent phenomenon.…”
Section: Serotonin Stress and The 5-ht2armentioning
confidence: 99%
See 1 more Smart Citation
“…Brouwer and Carhart-Harris name common inducers of stress, including social isolation, starvation, atypical breathing, sleep deprivation, extreme body temperature, pain, alongside canonical stressors such as sleep deprivation (Elmenhorst et al, 2012), hypoxia (Anju et al, 2011), and repeated shock (Dwivedi et al, 2005). Under the PiMS framing, when these stressors are combined with psychedelics, meditation, and other stimuli, a specific mental state capable of causing long-term changes can result.…”
Section: Pivotal Mental Statesmentioning
confidence: 99%
“…Firstly, chronic stress increases cortical 5-HT2AR expression and sensitivity to signaling ( [177][178][179][180] ; see 173 for a recent review). Such effects can be observed in response to physiological stressors such as deprivation of oxygen 181 , deprivation of sleep [182][183][184] , and inadequate nutrition 185 , and also in response to social/cognitive stress, such as recurring defeat 186 , rearing in isolation [187][188][189] and maternal separation 190,191 . Physiological or social deprivation may be a common factor here,…”
Section: -Ht2ar Agonism Via Endogenous 5-ht: the Central Role Of Stressmentioning
confidence: 99%